DIGITAL ECONOMY. CHALLENGES AND PROSPECTS - CHURIKANOVA, Olena; KABACHENKO, Dmytro; PRYKHODCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article delves into the prospects of digital economy development, examining its profound impact on various sectors including labor markets, productivity, e-commerce, financial technologies (fintech), and digital literacy levels. The digital economy is fundamentally reshaping global economic systems, driving innovation and growth while simultaneously posing significant challenges that require comprehensive solutions.One major focus is on the effects of automation and robotics, which are transforming traditional job roles and creating demand for new skill sets. The article highlights the growing need for advanced IT skills, data analysis, and cybersecurity expertise. This shift necessitates substantial adjustments in educational systems to prepare the workforce for the evolving demands of the digital age.The rapid expansion of e-commerce is another critical area of discussion. The convenience and efficiency of online shopping have revolutionized retail, but this growth also brings challenges such as data security, consumer protection, and regulatory compliance. The future of e-commerce will likely see further integration of technologies like augmented reality (AR) for virtual try-ons and drones for delivery, enhancing the consumer experience.Financial technologies, or fintech, are revolutionizing banking and finance by making financial services more accessible and user-friendly. Innovations in mobile payments, cryptocurrencies, and blockchain technology are disrupting traditional financial systems. The article explores the potential for AI integration in fintech to improve risk analysis, automate processes, and enhance transaction security.The article also addresses the critical issue of digital literacy. To ensure inclusive participation in the digital economy, it is imperative to enhance digital skills across all population segments. This includes continuous education and retraining programs to reduce the digital divide and boost workforce competitiveness.In conclusion, while the digital economy offers vast opportunities for economic growth and improved quality of life, addressing the associated challenges requires a multi-faceted approach involving governments, businesses, and society at large. Only through such collaborative efforts can the full potential of digital technologies be harnessed for global economic and social progress.
Keywords: digital economy; artificial intelligence; digital labor market; social protection; inclusiveness